Deformation Feature of TC4 Rod Based on Multi-line Triangle Pass System. Issue 10 (October 2017) - Meirong, Shuai; Hao, Liu; Haibin, Li; Zhiquan, Huang; Qingxue, Huang
Abstract: The rapid increase of the demand for titanium and titanium alloy rods with high strength and fine ductility results in the necessity to develop a multi-roller mill and a hot continuous rolling process. In this study, the authors proposed to produce TC4 alloy rod on Y-type mill with a multi-line triangle-round pass system. The deformation feature, rolling stability, and temperature distribution of TC4 alloy rod during the hot continuous rolling process were simulated with ANSYS software. The experiments were also conducted on Y-type mill. The results show that the multi-line triangle pass with concavity has a good centrality. Thus, the system can prevent TC4 rod from twisting or deviating from the rolling direction, and the stability of the rolled rod can be improved. Compared with the conventional flat triangle-round pass system, the proposed pass system obviously decreases the temperature gradient along the cross section of TC4 rod, thereby reducing the possibility of surface cracking, and improving the surface quality of the final product.